Green solvent approach for printable large deformation thermoplastic elastomer based piezoresistive sensors and their suitability for biomedical applications. Issue 20 (9th July 2016) - Gonçalves, Bruna F.; Costa, Pedro; Oliveira, Juliana; Ribeiro, Sylvie; Correia, Vitor; Botelho, Gabriela; Lanceros‐Mendez, Senentxu
ABSTRACT: Composites based on biocompatible thermoplastic elastomer styrene‐ethylene/butylene‐styrene (SEBS) as matrix and multi‐walled carbon nanotubes (MWCNT) as nanofillers show excellent mechanical and piezoresistive properties from low to large deformations. The MWCNT/SEBS composites have been prepared following a green solvent approach, to extend their range of applicability to biomedical applications. The obtained composites with 2, 4, and 5 wt % MWCNT content provide suitable piezoresistive response up to 80% deformation with a piezoresistive sensibility near 2.7, depending on the applied strain and MWCNT content. Composite sensors were also developed by spray and screen printing and integrated with an electronic data acquisition system with RF communication. The possibility to accurately control the composites properties and performance by varying MWCNT content, viscosity, and mechanical properties of the polymer matrix, shows the large potential of the system for the development of large deformation printable piezoresistive sensors. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 2092–2103 Abstract : Screen and spray printed thermoplastic elastomer styrene‐ethylene/butylene‐styrene based piezoresistive sensors have been developed following a green solvent strategy for large deformation applications. Biocompatible sensors with suitable piezoresistive response up to deformations of 10% have been achieved, allowing a wide range of applications.